From Nanostructure to Nano Biosensor: Institute of Nano Electronic Engineering (INEE), UniMAP Experience - U Hashim; K L Foo (Jurnal Fisika, 2011)
Nanostructure is defined as something that has a physical dimension smaller than 100 nanometers, ranging from clusters and/or to dimensional layers of atoms. There are three most important nanostructures that are extensively studied and researched in various organizations including Institute of Nano Electronic Engineering (INEE) in UniMAP. These include quantum dot, nanowire, and nanogap, which have been successfully designed and fabricated using in-house facilities available. These are subsequently used as a main sensing component in nanostructures based biosensor. This fabrication, characterization and testing job were done within four main interlinked laboratories namely microfabrication cleanroom, nanofabrication cleanroom, failure analysis laboratory and nano biochip laboratory.Â  Currently, development of Nano Biosensor is the main research focus in INEE. In principle, biosensor is an analytical device which converts a biological response into an electrical signal. Â  Keywords: Nanostructure, INEE , nanowire , nanogap and Nano Biosensor